Acorus calamus L. and Parthenium hysterophorus L. plant extracts potential as wood preservative against Gloeophyllum striatum decay fungus: Plant extracts potential as wood preservative against decay fungus (Indian Journal of Experimental Biology (IJEB), 2025)
This study aimed to assess the antifungal resistance of Acorus calamus and Parthenium hysterophorus plant extracts. Wood samples were treated with plant extracts at different concentrations: 0.25, 0.50, 1.00, 1.50, and 2%. For a period of 12 weeks, treated wood samples (Pinus roxburghii were tested for resistance to the brown rot decay fungus Gloeophyllum striatum. Wood samples treated with petroleum ether extract of A. calamus at 2% concentration showed the lowest mass losses (10.75%), and wood samples treated with the methanolic extract of P. hysterophorus showed the lowest mass losses (13.61%) at 2% concentration. Plant extracts of A. calamus and P. hysterophorus showed the highest antifungal activity and percentage fungus growth inhibition at 2.0% concentration. Maximum colonization was noticed for untreated wood samples, and the lowest was noticed at 2.0%. Antifungal properties of A. calamus and P. hysterophorus extracts were confirmed by a decay index test. After the decay test, chemical properties of wood samples were evaluated to confirm the efficiency of plant extracts, and it was observed that minimum losses of soluble extractives, lignin, and holocellulose of treated wood samples occurred at 2.0% concentration of extract. As per the findings of the present investigation, selected botanicals can be used for wood preservation and reducing the mass losses.